High-frequency circuit engineering - Nibler, F. (Ferdinand) (Institution of Electrical Engineers, 1996)
This book is aimed at both practising and postgraduate engineers who are interested in the particular problems of high-frequency circuit design. It covers network parameters and how to work with them, various approaches to the use of conductors, and it introduces a large number of circuits using active devices (transistors). It also deals extensively with computer supported problem solving, both with bespoke and off-the-shelf commercial software on PC or mainframe hosts. The problems of compatibility and noise are dealt with practically and in detail. There are chapters on high-frequency conductors, HF circuits with power transistors, unipolar and bipolar transistors in power stages, computer design and optimisation.